Nano-confined multi-synthesis of a Li–Mg–N–H nanocomposite towards low-temperature hydrogen storage with stable reversibility1. Issue 24 (28th June 2015) - Xia, Guanglin; Chen, Xiaowei; Zhou, Cuifeng; Zhang, Chaofeng; Li, Dan; Gu, Qinfen; Guo, Zaiping; Liu, Huakun; Liu, Zongwen; Yu, Xuebin
<x xml:space="preserve">Abstract</x> De-/re-hydrogenation of Li2Mg(NH)2 at a temperature as low as 105 °C and stable reversibility through up to 20 cycles are successfully achieved by the nanosize-induced effects by double-shelled hollow carbon spheres.